Paradiplomacy In Post-Conflict Federal States: A Case Study Of Somalia - WARSAME, ABDISHAKUR MOHAMED (İstanbul Kültür Üniversitesi, 2024)
In this thesis, the domestic structure of Somalia's post-conflict federal structure is comprehensively analyzed in order to reach the aim of examining the emergence, development, and current status of paradiplomacy phenomenon within the country's intricate post-conflict settings. Employing a comprehensive review of diverse academic and policy-oriented materials through a qualitative lens, the thesis adopts El-Dessouki's (2018) explanatory framework to scrutinize how domestic structural variables—legal frameworks, autonomy levels, intergovernmental dynamics, and institutionalization—shape paradiplomatic engagements. It uncovers that, notwithstanding constitutional intents to centralize foreign policy, the interplay of constitutional ambiguities, historical legacies, and post-conflict governance challenges fosters a fertile ground for subnational foreign engagements, further intensified by the friction between the Federal Member States' autonomy aspirations and the Federal Government's sovereignty assertions. Thus, the structural analysis given in this thesis, through underlining the central role of domestic structural variables in molding paradiplomacy within the context of post-conflict federal settings, unveils interconnected the dimensions and parameters of paradiplomacy in Somalia.
Çatışma Sonrası Federal Devletlerde Paradiplomasi: Somali Örneği
Yüksek lisans tezi.
Keywords: Federal Structure; Paradiplomacy; Post-Conflict Federalism; Somalia